Grafting poly (amidoamine) dendrimer-modified silica nanoparticles to graphene oxide for preparation of a composite and curing agent for epoxy resin. (22nd September 2017) - Azimi, Reza; Roghani-Mamaqani, Hossein; Gholipour-Mahmoudalilou, Meysam
Abstract: A new multi-component curing agent for epoxy resin with graphene oxide (GO) core and poly (amidoamine) (PAMAM) dendrimer-grafted silica nanoparticles was synthesized which is able to cause a considerable thermal stabilization of epoxy resins due to its dendritic amino-functionalization. Hyperbranched PAMAM-grafted silica nanoparticles (SD) were prepared and attached at the surface of GO to prepare the composite and curing agent (GSD). Then, epoxy resin was cured in the presence of different amounts of GSD and the final products were compared with ethylenediamine-cured epoxy resin (E) in their char contents. Successful functionalization of silica nanoparticles and attachment of SD at the surface of GO were evaluated by Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, X-ray diffraction, and thermogravimetric analysis (TGA). TGA results showed that total dendrimer content in SD and char residue of GSD are 14.4 wt % and 60.9%, respectively. Char residue and decomposition temperature are higher for composites. Covering of GO with SD was approved by scanning and transmission electron microscopies. Graphical abstract: Highlights: A curing agent for epoxy resin, GO covered with PAMAM dendrimer-grafted silica nanoparticles (SD), was synthesized. SD was attached at the surface of GO for preparation of GSD as the curing agent with dendritic amino-functionalization. Epoxy resin was cured with different amounts of GSD and thermal stability of the final products was evaluated. Char residue and decomposition temperature are higher for composites compared with ethylenediamine-cured epoxy resin.